PENGARUH STRATEGI PROMOSI DAN HARGA TERHADAP KEPUASAN PELANGGAN JASA INTERNET SERVICE ASNET, KUALITAS PELAYANAN SEBAGAI VARIABEL MODERASI PADA PT. USAHA ADI SANGGORO - Marlia Rizky, Kiki; Ekawati, Christina (Jurnal Gici Jurnal Keuangan dan Bisnis, 2025)
This study aims to analyze the influence of promotion strategies and price strategies on customer satisfaction of Internet Service Asnet services at PT. Adi Sanggoro's business, with service quality as a moderation variable. The background of this research is based on the importance of the role of promotion and competitive pricing in improving customer satisfaction in the midst of increasingly fierce competition in the internet service provider industry. The method used in this study is a quantitative approach with data collection techniques through questionnaires distributed to Asnet customers. Data analysis was carried out using the data analysis model used is Pathh Analisys Data to determine the role of service quality in strengthening or weakening the relationship between free variables and customer satisfaction. The results of the study show that promotion strategies and pricing strategies have a positive and significant effect on customer satisfaction. In addition, the quality of service has been shown to moderate the relationship between promotional strategies and pricing strategies to customer satisfaction significantly. This finding has implications for the management of PT. Adi Sanggoro's efforts to continue to improve the effectiveness of promotions, set competitive prices, and maintain and improve service quality are the main strategies in maintaining customer loyalty.